Abstract ID: 130 Energy response correction for EPID dosimetry in photon radiation therapy. (October 2017) - Takei, Hideyuki; Isobe, Tomonori; Watanabe, Yusuke; Hasegawa, Tomoyuki; Sato, Eisuke; Hara, Hidetake; Muraishi, Hiroshi; Sakae, Takeji
Abstract : Electronic portal imaging device (EPID) is a popular tool for a verification of the patient setup for radiation therapy. Recently, it is grabbing attention as a tool for in vivo dosimetry. It detects therapeutic photons which penetrated the patient body to acquire an image. Conversion to absorbed dose is required from the digital pixel value. However, the response of the EPID is susceptible to the energy spectrum changes through the body[1], [2] . The purpose of this study was to perform the energy response correction of the EPID image using Monte Carlo simulation (MC) to improve the accuracy of the EPID dosimetry. Geant4.9.6 patch04 was used for the MC with a combination of a HTCondor 7.6 parallel computing software. The MC simulated the 6 and 10 MV photon beams from Trilogy (Varian Medical Systems) linear accelerator. The EPID response to the energy spectrum was evaluated. CT DICOM data set of a chest phantom was imported to the MC, and the simulated EPID images were acquired after irradiating 6 and 10 MV photon beams. The measurement was performed with the same setup as the MC and obtained the EPID images. The energy response was corrected to obtain the absorbed dose and compared with that measured with 2D array detector (PTW) as a reference. EPID was more sensitive to the photons penetrated the mediastinum than those penetrated the lung due to the contamination of the scattered photons with the energy of <0.1 MeV. The maximum differences between the doses measured with EPID and those measured with 2D array was 5.8% in mediastinum area with the 6 MV photon beam. The difference was less than 1.5% in average in lung area. The agreement of the corrected EPID dose and 2D array improved within 2.5% in mediastinum area for the 6 MV beam. The results showed that the corrected EPID dose agreed well with that measured with 2D array detector. The response correction using MC improved the accuracy of the EPID dosimetry.